Вербализация каритивной семантики в русском и польском экономическом дискурсе - Bahanova, Aigul; Kilevaya, Lyudmila (Acta Polono-Ruthenica, 2016)
The paper analyzes the linguistic means incarnation karitive semantics in Russian and Polish economic discourse. The material o f the study uses data Kazakh Russian-language newspapers and Polish newspapers. Karitive semantics interpreted as the nuclear part o f the category o f lackness. In Russian and Polish speech activity on economics, used identical language units. This is due to a common origin o f language systems, dating back to the pre-Slavic language, and with respect to the interpretation o f the general problems o f the economy in Kazakhstan and Poland.